Osservazioni sulla geomorfologia della Terra Vittoria settentrionale, Antartide. - BARONI, CARLO (Società Geografica Italiana, 1994)
Notes on Geomorphology of Northern Victoria Land, Antarctica. Northern Victoria Land shows phenomena of residual ancient morphology, glacial troughs, elements of alpine moorphology, coastal reliefs and volcanic buildings little eroded.